Cropping events of maize in Cordoba-Colombia - Jiménez, Daniel; Delerce, Sylvain Jean; Dorado, Hugo Andres; Cock, James H.; Muñoz, Luis Armando; Agamez, Alejandro; Jarvis, Andy (International Center for Tropical Agriculture, 2019)
The data represent 804 cropping events of maize planting in Córdoba - Colombia from 2013 to 2016. Each cropping event has information on climate, soil, and agronomic management. The data was collected with the aim of determining the factors that affect the variation in the yield of maize. The dataset was created through a collaboration project among International Center for Tropical Agriculture CIAT, the Colombian National Cereals, and Legumes Federation (FENALCE) and the Colombian Ministry of Agriculture and Rural Development (MADR).